Factors affecting association between pain severity and physical activity among people with low back pain - Saltychev Mikhail; Hellgren Henri; Juhola Juhani (LIPPINCOTT WILLIAMS & WILKINS, 2025)
The aim was to identify factors, which may affect the relationship between physical activity and pain severity among patients with low back pain (LBP). It was a cross-sectional survey-based study among 1332 consecutive patients with LBP. Linear regression models were employed. Patients were 47.6 years old and 64% were women. For the entire sample, pain severity and the intensity of physical activity were negatively associated. Higher physical activity was associated with younger age, higher educational level, normal weight and optimal perceived general health. Sex, smoking, marital status and occupation did not demonstrate significant interactions on the association. The severity of disability showed paradoxical effect on the relationship between pain and physical activity - severe disability was associated with increase in physical activity.